Exploring a novel turbulence model: The Chi-square/inverse Gamma approach for enhanced free space optics (FSO) communication - Stanojević, Nenad; Banđur, Đoko; Mosurović, Lazar; Spalević, Petar; Panić, Stefan (Oficyna Wydawnicza Politechniki Wrocławskiej, 2024)
The manuscript introduces a novel turbulence model for free space optics (FSO) communication, constructed through the amalgamation of two distinct statistical models, rooted in the scintillation theory. A closed-form expression for the probability density function (PDF) and cumulative distribution function (CDF) of the turbulence channel, specifically the Chi-square/inverse Gamma distribution, was deduced. Further the influence of zero boresight pointing errors on the performances of FSO transmission over the obtained atmospheric turbulence channel has been considered. To delve into the intricacies of the channel, an examination of the average bit error rate (ABER) was undertaken as an evaluative metric for the transmitted signal’s quality. The ABER analysis was specifically conducted within the framework of IM/DD (intensity modulation and direct detection) and OOK (on-off keying), considering diverse sets of system parameters and across various turbulence scenarios. In the same manner, ABER analysis has been carried out for the subcarrier intensity modulation (SIM) with differential phase-shift keying (DPSK).
Optica Applicata, Vol. 54, 2024, nr 3, s. 337-351
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; turbulence modelling; scintillation theory; Chi-square/inverse Gamma distribution; free space optics (FSO); average bit error rate (ABER)